Interpersonal communication during conflict between couples of different nationalities - Antolin, Jennifer C. (2004)
"Interpersonnal Communication During Conflict Between Couples of Different Nationalities" was a descriptive study on the role of interpersonal communication on the relationship of married couples of different nationalities during times of conflict. It looked into their common causes of conflicts, behevior during conflict, cultural factors that affect their conflict and conflict management, initiator of communication, how they resolve conflicts, duration of conflicts, and factors that lead to resolution or that maintain the couples's relationship. Ten(10) married couples of different nationalities such as Japanese and Filipino, American and Filipino, Swiss and Filipino, Scottish and Filipino, British and Filipino that have lived together for at least a year and spent most of their time together were the respondents of the study. They were interviewed and observed for the study. The narrative type of analysis was used in analyzing and interpreting the findings from the interviews and observations. The study discovered that the common causes of conflict were upbringing of the children, religion, incompatible ideas, deeds and attitudes, and work. The couples communicate their conflicts in different ways- either they argued or they fill silent. These conflicts could last from a few minutes to one(1) month. It did not really matter who initiated resolution but most of the conflicts were resolved through talking things over after cooling their emotions down. The biggest factors that triggered resolution between the couples were their children and love for each other. Results of the study showed that interpersonal communication was an effective tool for couples to resolved their conflicts. Moreover, the different cultural backgrounds and orientations of the couples affected the way they managed their conflicts through the strategies or conflict styles they used such as dominating integrating, compromising, obliging and avoiding --Author's abstract.
Thesis (Bachelor of Arts in Communication) -- University of the Philippines Baguio, 2004.
Includes bibliographical references.
Keywords: Interpersonal communication; Marital conflict; Conflict management